The Adaptive Significance of Flash Behavior: A Bayesian Model - Sherratt, Thomas N.; Loeffler-Henry, Karl (Frontiers in Ecology and Evolution, 2022)
Some cryptic animals have conspicuous color patches that are displayed when they move. This “flash behavior” may serve several functions, but perhaps the most widely invoked explanation is that the display makes it harder for the signaler to be found by predators once it has settled. There is now some experimental evidence that flash behavior while fleeing can enhance the survivorship of prey in the manner proposed. However, to date there has been no explicit mathematical model to help understand the way in which flash displays might interfere with the search process of predators. Here we apply Bayesian search theory to show that the higher the conspicuousness of a prey item, the sooner a predator should give up searching for it in an area where it appears to have settled, although the relationship is not always monotonically decreasing. Thus, fleeing prey that give the impression of being conspicuous will tend to survive at a higher rate than prey seen to flee in their cryptic state, since predators search for flashing prey for an inappropriately short period of time. The model is readily parameterized and makes several intuitive predictions including: (i) the less confident a predator is that a prey item has settled in a given area, the less time it will search there (ii) the more conspicuous the flash display, the greater its effect in reducing predation (iii) flash behavior will especially benefit those prey with intermediate level of crypsis when at rest and (iv) the success of flash displays depends on the predator being uncertain of the prey’s resting appearance. We evaluate the empirical evidence for these predictions and discuss how the model might be further developed, including the incorporation of mimicry which would maintain the deception indefinitely.